Work-Life Balance Sebagai Strategi Retensi Dengan Analisis Mediasi Kepuasan Kerja Dalam Konteks Industri Jasa - Muhammad Faisal Anwar; Zulganef Zulganef (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the effect of work-life balance on employee retention with job satisfaction as a mediating variable at PT Trans Dana Profitri. The background of this study is the phenomenon of increasing employee turnover in recent years, indicating a serious challenge in retaining the workforce. Work-life balance is considered an important factor that can increase employee loyalty, however, the results of previous studies still show different findings, so job satisfaction is included as a mediating variable to explain the relationship more comprehensively. The study used a quantitative approach with a survey method and an explanatory design. The research sample of 125 respondents was determined using the Slovin formula from a total population of 182 employees. The data collection instrument was a questionnaire with a five-point Likert scale, which covered the dimensions of work-life balance, job satisfaction, and employee retention. Data were analyzed using path analysis with partial and simultaneous tests, as well as the Sobel test to examine the mediating role. The results showed that work-life balance had a positive and significant effect on job satisfaction and retention. Job satisfaction also had a significant effect on retention and was proven to partially mediate the relationship between work-life balance and retention. This research confirms that effective retention strategies need to combine work-life balance policies with efforts to increase job satisfaction through career development, task variety, and organizational support.